2013
DOI: 10.1021/ic400357p
|View full text |Cite
|
Sign up to set email alerts
|

Easy Access to Silicon(0) and Silicon(II) Compounds

Abstract: Two different synthetic methodologies of silicon dihalide bridged biradicals of the general formula (L(n)•)2SiX2 (n = 1, 2) have been developed. First, the metathesis reaction between NHC:SiX2 and L(n): (L(n): = cyclic akyl(amino) carbene in a 1:3 molar ratio leads to the products 2 (n = 1, X = Cl), 4 (n = 2, X = Cl), 6 (n = 1, X = Br), and 7 (n = 2, X = Br). These reactions also produce coupled NHCs (3, 5) under C-C bond formation. The formation of the coupled NHCs (L(m) = cyclic alkyl(amino) carbene substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 54 publications
0
58
0
4
Order By: Relevance
“…[8] Calculations suggest that Kiras silaallene better should be described as a silylone. [12] A second silylone was reported by Driess et al recently. [1] In contrast, further calculations by Kosa 2 Si showed that a silylone with two NHC ligands should experimentally be feasible.…”
Section: In Memory Of Daniel Kostmentioning
confidence: 92%
See 2 more Smart Citations
“…[8] Calculations suggest that Kiras silaallene better should be described as a silylone. [12] A second silylone was reported by Driess et al recently. [1] In contrast, further calculations by Kosa 2 Si showed that a silylone with two NHC ligands should experimentally be feasible.…”
Section: In Memory Of Daniel Kostmentioning
confidence: 92%
“…There are small but significant differences in the bond lengths of Si1 À C1 (1.8454 (2) Figure 5). [23,12] Thus this might be attributed to packing effects. [23] However, compounds with dimethyl groups instead of the cyclohexyl group do not show significant differences in these values, both in the silylone and the germylone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this knowledge of stability (SiCl 2 > SiBr 2 ), more electronegative substituents on silicon should assist in the stabilization of these types of biradicals. However, attempts to generate the SiF 2 derivative were unsuccessful, 34 although it appears to be a viable synthetic target.…”
Section: Introductionmentioning
confidence: 99%
“…[29] In contrast, housane 2' exhibits a three-membered ring annulated to an almost perpendicular lying four-membered heterocycle with a PÀP banana single bond (P1ÀP2 2.167 ), PÀN single bonds (N1ÀP1 1.757, N2ÀP1 1.797, N1ÀP2 1.792 ) and a localized C=O double bond. [18,19,[31][32][33][34] Also the natural orbital occupation numbers (HOMO: 1.44 and LUMO: 0.56 e) clearly indicate open shell singlet biradical character. NBO occupation of p atomic orbitals perpendicular to the five-membered ring amounts to 5.7 e (C 0.84, N1 1.70, P1 0.66, N2 1.60, P2 0.90).…”
mentioning
confidence: 97%